2023
DOI: 10.3389/fcimb.2023.1274175
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant strains of Mycobacterium tuberculosis: cell envelope profiles and interactions with the host

Alyssa Schami,
M. Nurul Islam,
John T. Belisle
et al.

Abstract: In the past few decades, drug-resistant (DR) strains of Mycobacterium tuberculosis (M.tb), the causative agent of tuberculosis (TB), have become increasingly prevalent and pose a threat to worldwide public health. These strains range from multi (MDR) to extensively (XDR) drug-resistant, making them very difficult to treat. Further, the current and future impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the development of DR-TB is still unknown. Although exhaustive studies have been conducted depic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 145 publications
0
11
0
Order By: Relevance
“…Previous studies suggests that PDIMs may be a critical component to protect the impermeability of the M.tb cell envelope, as PDIMs deficiency is linked to increased susceptibility of mycobacteria to anti-TB drugs. 3, 1113 However, there are very few studies directed at the PDIMs levels in DR- M.tb strains. 15 Here, we performed an exhaustive lipid extraction on three DS-, three MDR-, and five pre-XDR- M.tb strains and analyzed their total lipid extracts using TLC with validation by LC-MS. Our TLC analysis showed that PDIMs levels increase as the drug resistance profile increases, where pre-XDR M.tb strains had the largest increase in PDIMs levels when compared to DS- M.tb strains H 37 R v , Erdman, and CDC1551 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggests that PDIMs may be a critical component to protect the impermeability of the M.tb cell envelope, as PDIMs deficiency is linked to increased susceptibility of mycobacteria to anti-TB drugs. 3, 1113 However, there are very few studies directed at the PDIMs levels in DR- M.tb strains. 15 Here, we performed an exhaustive lipid extraction on three DS-, three MDR-, and five pre-XDR- M.tb strains and analyzed their total lipid extracts using TLC with validation by LC-MS. Our TLC analysis showed that PDIMs levels increase as the drug resistance profile increases, where pre-XDR M.tb strains had the largest increase in PDIMs levels when compared to DS- M.tb strains H 37 R v , Erdman, and CDC1551 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that a deficiency in the hydrophobic cell envelope lipid PDIMs results in increased cell envelope permeability and greater susceptibility of mycobacteria to anti-TB drugs. 3, 1113 However, there are very few studies indicating increased levels of PDIMs in DR- M.tb strains. 15 Here we biochemically examined the cell envelope lipid composition of 11 M.tb strains that range from DS (including H 37 R v , Erdman, and CDC1551) to MDR and pre-XDR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…61]. Multi-drug resistant Mtb have thicker cell envelopes[62]. INH caused many, but not all, Mtb cells to have thickened cell envelopes.…”
mentioning
confidence: 99%